CHARACTERIZATION OF NATURAL ZEOLITE BY X-RAY DIFFRACTOMETER - Suminta, Supandi (Jurnal Zeolit Indonesia, 2006)
An identification of framework mineral structure of natural zeolit Bayah, Lampung and Malang was carried out by Reitveld methods. X ray diffraction intensity of Natural zeolit was measured by an X-Ray Diffractometer (XRD). The refinement of Clinoptilolite and Mordenite phases have been carried out and the results of refinement show that in Bayah and Lampung were Clinoptilolite phase ( space group C2/m No.12, Bravais lattice is Base-Centered and crystal system is monoclinic) and lattice parameter are a = 17,69(2) Ã , b = 17,92(1) Ã dan c = 7,422(9) Ã respectively (Bayah zeolite) and a = 17,69(2) Ã , b = 17,92(1) Ã dan c = 7,422(9) Ã respectively (Lampung zeolite) and pore size are S10R = 10,685 Ã dan S8R = 8,193 Ã . While Malang zeolites phase (space group Cmcm No.63, Bravais lattice is Base Centered and crystal system is orthorombic) was Mordenite phase and the lattice parameter are a = 18,115(8) Ã , b = 20,520(9) Ã dan c = 7,515(2) Ã . The pore size are S8R = 11,43 Ã dan S12R = 7,730 Ã . Material of natural zeolit from Bayah and Lampung have Cation Exchange Capasity (CEC) bigger than Malang (acording to results of the framework structure analysis).